Is all greenspace created equal? Assessing the relationship of public parks and greenness on academic achievement in Washington state - Lea Fortmann; Isha Rajbhandari (PLoS ONE, 2026)
In educational environments, proximity to greenspace can increase concentration, attentiveness, self-discipline, improve classroom engagement, and support cognitive development. This study contributes to this growing literature by examining the potential benefits associated with public parks on academic performance across different grade levels in four counties in western Washington state, USA. We use a five-year panel data set to assess the impact of a school’s proximity to a public park on the percentage of students in each grade who meet or exceed proficiency standards for statewide assessment tests while controlling for general greenness, along with a number of socioeconomic and demographic factors. Our results suggest that having a public park within 800 meters of the school is associated with an increase in the percentage of students that meet or exceed the standard for language arts and math standardized tests for middle schoolers. The local greenness of the school grounds and surrounding area, measured by NDVI, had no impact on test scores. This suggests that the parks themselves could have a positive relationship, beyond increased exposure to greenness, and potentially provide academic benefits to students. We do not find a significant impact of a school’s proximity to public parks for elementary or high school students, which we hypothesize could be for various reasons. Though the literature on the benefits associated with public parks is well established, this is the first study, to our knowledge, to investigate their potential relationship with educational performance.